Individually-Typological Peculiarities of Personality Self-Discipline and Self-Actualization Correlation - S S Kudinov (Peoples' Friendship University of Russia (RUDN University), 2013)
The scientific credence to the personality self-actualization and self-discipline correlation is given in the article. Within the frame of a system-defined research, different individually-typological peculiarities of self-discipline are highlighted and characterized. Their comparative analysis with the personality self-actualization is conducted.